2020
DOI: 10.2118/201193-pa
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Behavior of Reservoirs with Convolutional and Recurrent Neural Networks

Abstract: Summary Recent experience in applying recurrent neural networks (RNNs) to interpreting permanent downhole gauge records has highlighted the potential utility of machine learning algorithms to learn reservoir behavior from data. The power of the RNN resides in its ability to retain information in a form of memory of previous patterns and information contained in the previous behavior of phenomena being modeled. This memory plays a role of informing the decision at the present time by using what h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There are also other interesting literatures (Nait Amar et al 2018Navrátil et al 2019;Alakeely and Horne 2020;Ng et al 2021) that discuss and present the use of ML methods in the establishment of proxies of numerical models in petroleum domain, especially for reservoir engineering. Regarding this, there is a riveting insight being provided by Nait Amar et al (2018) about the modeling of proxies, which is the difference between static and dynamic proxy models.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other interesting literatures (Nait Amar et al 2018Navrátil et al 2019;Alakeely and Horne 2020;Ng et al 2021) that discuss and present the use of ML methods in the establishment of proxies of numerical models in petroleum domain, especially for reservoir engineering. Regarding this, there is a riveting insight being provided by Nait Amar et al (2018) about the modeling of proxies, which is the difference between static and dynamic proxy models.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished with learnable kernels which can be identified with small windows that have the same dimensionality as the input data (i.e., 2D for images, 3D for volumes). They have been successfully applied in many tasks regarding earth science disciplines (Alakeely and Horne 2020;Jo et al 2020;Pan et al 2020), and particularly in the field of digital rocks (Guiltinan et al 2020a;Mosser et al 2017a, b;Chung et al 2020;Bihani et al 2021;Santos et al 2018b). These data-driven models have also been useful for solving flow (Santos et al 2020b;Wang et al 2021a, b;Alqahtani et al 2021), successfully modeling the relationship between 3D microstructure and flow response much more accurately than empirical formulas that depend only on averaged properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors analyzed different feature combinations and highlighted the optimal set providing the maximum quality of predictions. In the study [5], the authors compared the predictive capabilities of convolutional (CNN) and recurrent (RNN) neural networks to simulate the reservoir behavior. The authors demonstrated that both networks could capture the interference between multiple wells at the same reservoir.…”
Section: Introductionmentioning
confidence: 99%